Keberadaan Pasar Tradisional di Jakarta Sebagai Destinasi Wisata - Sulistiyo, Tri Djoko; Gantina, Devita; Haryono, Joko; Rachmatullah, Adam; Aditya, Michael Khrisna (Jurnal Ilmiah Pariwisata, 2025)
Traditional markets in Jakarta, such as Tanah Abang Market, Jatinegara Market, and Senen Market, have great potential as sustainable tourist destinations. However, these markets face various challenges related to infrastructure, cleanliness, and suboptimal management. This study aims to analyze the potential of traditional markets as tourist destinations and identify factors that influence their attractiveness and management. The method used is a qualitative approach with in-depth interviews with traders, visitors, and market managers, as well as field observations of the physical and social conditions of the market. The results of the study indicate that the main attraction of traditional markets lies in the authentic local atmosphere, social interaction between traders and buyers, and the diversity of cultural products. However, inadequate infrastructure, poor cleanliness, and an uncoordinated management system reduce visitor comfort. In conclusion, traditional markets have great potential as tourist destinations, but require infrastructure improvements, more professional management, and training for traders to improve services. The suggestion of this study is the need for more inclusive policies and a balanced approach between modernization and preservation of local culture so that traditional markets can develop as sustainable tourist destinations. Keywords: traditional market, tourist destination, infrastructure, cleanliness, cultural preservation